2011
DOI: 10.1103/physrevc.84.064306
|View full text |Cite
|
Sign up to set email alerts
|

Four-body resonances of7B using the complex scaling method

Abstract: We study the resonance spectroscopy of the proton-rich nucleus 7 B in the 4 He + p + p + p cluster model. Many-body resonances are treated under the correct boundary condition as Gamow states using the complex scaling method. We predict five resonances of 7 B and evaluate the spectroscopic factors of the 6 Be-p components. The importance of the 6 Be(2 + )-p component is shown in several states of 7 B; this is a common feature of 7 He, a mirror nucleus of 7 B. For only the ground state of 7 B, the mixing of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 29 publications
(79 citation statements)
references
References 49 publications
3
74
1
1
Order By: Relevance
“…It is found that the present calculations agree with the observed energy levels. We, furthermore, predict many resonances for 6 Be, 7 B, and 8 C. In the previous analysis [14], we discussed the structures of 6 Be and 7 B in detail, such as the spatial properties of extra protons, the configurations and the mirror symmetry. It was found that the 6 Be structures are similar to those of a mirror nucleus 6 He.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is found that the present calculations agree with the observed energy levels. We, furthermore, predict many resonances for 6 Be, 7 B, and 8 C. In the previous analysis [14], we discussed the structures of 6 Be and 7 B in detail, such as the spatial properties of extra protons, the configurations and the mirror symmetry. It was found that the 6 Be structures are similar to those of a mirror nucleus 6 He.…”
Section: Resultsmentioning
confidence: 99%
“…In COSM, the asymptotic boundary condition of the wave functions for proton emissions is correctly described [14,27,38]. For 8 C, all the channels of 8 C, 7 B + p, 6 Be + 2p, 5 Li + 3p, and 4 He + 4p are automatically included in the total wave function J in Eq.…”
Section: Complex-scaled Cosmmentioning
confidence: 99%
See 3 more Smart Citations